The potential interplay between G-quadruplex and p53: their roles in regulation of ferroptosis in cancer - Zhang, Lulu; Lu, Yi; Ma, Xiaoli; Xing, Yuanxin; Sun, Jinbo; Jia, Yanfei (Frontiers in Molecular Biosciences, 2022)
Ferroptosis is a novel form of regulated cell death trigged by various biological processes, and p53 is involved in different ferroptosis regulations and functions as a crucial regulator. Both DNA and RNA can fold into G-quadruplex in GC-rich regions and increasing shreds of evidence demonstrate that G-quadruplexes have associated with some important cellular events. Investigation of G-quadruplexes is thus vital to revealing their biofunctions. Specific G-quadruplexes are investigated to discover new effective anticancer drugs. Multiple modulations have been discovered between the secondary structure G-quadruplex and p53, further influencing the ferroptosis in cancer. G-quadruplex binds to ferric iron-related structures directly and affects the p53 pathways as well as ferroptosis in cancer. In addition, G-quadruplex also interacts with p53 indirectly, including iron-sulfur cluster metabolism, telomere homeostasis, lipid peroxidation, and glycolysis. In this review, we summarized the interplay between G-quadruplex and p53 which focused mainly on ferroptosis in cancer to provide the potential understanding and encourage future studies.